Viewpoint: An Exploration of How Natural Resource Management (NRM) Discourse is Integrated into Key Pedagogic Texts - Yvonne Nsubuga (Environmental Association of Southern Africa, 2006)
Natural resource management (NRM) education has the potential to improve the quality and relevance of rural education in South Africa. For this potential to be realised, the various educational resources that are commonly used by teachers and learners in rural schools need to incorporate natural resource management knowledge. Using Bernstein's concepts of classification and his theories on recontextualisation, a content analysis study was carried out to compare the level of NRM integration within the Grade 10 Life Sciences syllabus, and a Grade 10 Life Sciences textbook. Results from the analysis of the syllabus showed that overall only 9% of all the knowledge statements analysed had a strong link to NRM and related issues. The highest percentage of such sentences was found in the Core Knowledge section of the syllabus (21%). For the textbook, only 8% of the analysed items had a strong link to NRM and related issues, with the highest percentage of such items occurring in the Suggested Activities section (16%). However, the level of NRM integration in both documents increased considerably when sentences that had only an implicit link to NRM and related issues were included. It was concluded that both documents provide ample opportunities for NRM learning, although the extent to which this occurs varies among their different sections. The recontextualising role of the Grade 10 Life Sciences textbook was reflected in its relatively higher level of NRM integration in the Suggested Activities category, and in the Glossary category. This study highlights the need for further strengthening of the position of NRM within the Grade 10 Life Sciences syllabus, and for more Bernstein-based research to inform South Africa's curriculum reform initiatives in environmental education.